Peter Lilienthal. A Cinema of Exile and Resistance. - Bongers, Wolfgang (Imagofagia, 2021)
Sobre Claudia Sandberg. Peter Lilienthal. A Cinema of Exile and Resistance, 2021, New York, Oxford: Berghahn Books, 208 pp., ISBN 9781-80073-091-2.